Description of Creep Strain Anisotropy of the Lignostone in The Form of Tensor Polynomial and a Modified Tensor Polynomial - Czech, M. (Engineering Transactions, 1995)
The results of creep investigations of the lignostone under axial compression are presented in the paper. The specimens were cut off from the lignostone bars at different angles to the main orthotropy axis. The tensor polynomial in the form (1.2) and the modified tensor polynomial in the form (1.3) were used to describe creep strain for different angles of cutting the specimens. The first and the third terms of the polynomials provide a correct description in both methods, however a better description has been obtained for the second one.